PENGARUH STRATEGI RODA KEBERUNTUNGAN MATERI JENIS – JENIS PEKERJAAN DAN PENTINGNYA SEMANGAT KERJA TERHADAP PRESTASI BELAJAR IPS SISWA SD KELAS III SEMARANG - Aninda Cintami Rahayu; Sutrisno Sutrisno; Mudzanatun Mudzanatun (Jurnal Lensa Pendas, 2019)
This study aims to determine whether or not there is an influence of the material fortune wheel material on types of work and the importance of working spirit towards the achievement of social studies learning grade III of SDN Jomblang 01 semarang. The research with pre-experimental design design. The research descriptions used are one-group pre-test post-test design. The population of this study is all student of grade IIIA SDN Jomblang 01 Semarang. Sampling technique used is Non Probability. The data in this study were obtained through test and non-test techniques. Based on the analysis of test known thitung more than ttabel (13,90004 > 2,021) then H0 rejectes and Ha accepted. So it can be conclude that there is influence of wheel strategy of luck material of the kinds of work and the importance of work morale toward student achievement of social studies learning grade III of SDN Jomblang 01 Semarang